Influence of Personality on Shape-Based Design Activities. (2nd May 2019) - Filippi, Stefano; Barattin, Daniela
Abstract : As the literature demonstrates, designers' personality influences design activities like different ways to represent environments and/or products, technological advances, etc.. Nevertheless, an exhaustive analysis on the influence of personality on design activities involving different representations is missing. This research explores this gap by studying this influence on specific design activities, the shape-based ones (i.e., analysis of specific shapes and highlighting of functions suggested by them). People showing different personalities undergo tests where they carry out design activities exploiting several representations. The results confirm the influence of personality on shape-based design activities and allow highlighting different keys to interpret and exploit these results. Thanks to the results of this study, researchers can increase their knowledge about subjective aspects of design as well as about how these aspects coexist with classic and emerging representations. As well, designers can try to maximize the effectiveness of their efforts by selecting the best combinations of personality, representations, and characteristics of the expected design results time by time.